Melt-quenched vanadium pentoxide-stabilized chitosan nanohybrids for efficient hydrazine detection. Issue 20 (20th September 2021) - Singh, Jay; Singh, Kshitij RB; Kumar, Manish; Verma, Rahul; Verma, Ranjana; Malik, Priya; Srivastava, Saurabh; Singh, Ravindra Pratap; Kumar, Devendra
Abstract : This study reports the synthesis of melt-quenched and hydrothermally derived V2 O5 (n-V2 O5 ) ex situ grafted onto the chitosan biopolymer as an organic–inorganic nanohybrid material for the determination of N2 H4 . Abstract : Nanocrystalline low-dimensional nanostructured vanadium pentoxide (n-V2 O5 ) nanoparticles were synthesized using a hydrothermal and melt-quenching approach without using any reducing agent, acids/bases, and hazardous solvents. Further, the synthesized V2 O5 nanoparticles were successfully dispersed in a chitosan (CS) solution for fabricating an organic–inorganic nanohybrid matrix for the electrocatalytic determination of hydrazine to avoid human exposure. Furthermore, this study was supported by various sophisticated tools to characterize the synthesized V2 O5 and V2 O5 –CS films, namely UV-Vis, PL, FTIR, XRD, SEM, AFM, TEM, and EDX. The V2 O5 –CS nanohybrid showed a substantial sensing strength when deposited onto an indium-tin-oxide (ITO)-coated glass substrate without ultrasonication and studied using amperometry and cyclic voltammetry techniques. Thus, the electrochemical responses against various hydrazine concentrations obtained from the fabricated V2 O5 –CS/ITO electrode demonstrated high sensitivity, a low detection limit, a quick response time, and a wide linear range of 50.48 μA μM −1 cm −2, 0.084 mM, 20 seconds, and 2–22 mM at a 50 mV scan rate, respectively. Hence, the utilization of V2 O5 –CS-based inorganic–organic nanohybrid materials fabricates a robust sensing system and a favorable sensing platform with wide applications towards the development of electrochemical sensor devices.